Anti-de Sitter holography in di?erent coordinates - Hernández Moreno, Ricardo Alfonso [UNESP] (2013)
The goal of this work is to show the signi?cance of the choice of coordinates system and signature to describe the Anti-de Sitter space within AdS/CFT Correspondence. In order to do so, we will show how to calculate AdS/CFT correlators in di?erent coordinates from the gravity side of the correspondence. In particular, we present the general procedure to ?nd the bulk-to-boundary propagators for scalar, gauge and spinor ?elds using Witten’s method in Poincaré coordinates with Euclidean signature. We also show the calculations ofn-point functions for a classical interacting scalar ?eld in AdS at tree level and compare the results with the CFT constraints. To compare the implications of working in di?erent coordinates, we recalculate the propagators for the scalar ?eld in Global coordinates. Finally, we show the calculations of bulk-to-boundary propagator for a 3-form ?eld living in 'AdS IND. 7' in both Poincaré and Global coordinates